2014
DOI: 10.1002/hep.27232
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept blocks inflammatory responses orchestrated by TNF-α to promote transplanted cell engraftment and proliferation in rat liver

Abstract: Engraftment of transplanted cells is critical for liver-directed cell therapy but most transplanted cells are rapidly cleared from liver sinusoids by proinflammatory cytokines/chemokines/receptors after activation of neutrophils or Kupffer cells. To define whether TNF-α served roles in cell-transplantation-induced hepatic inflammation, we used TNF-α antagonist, etanercept, for studies in syngeneic rat hepatocyte transplantation systems. After cell transplantation, multiple cytokines/chemokines/receptors were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…The disparate findings with TNF signaling in promotion of regeneration after partial hepatectomy as opposed to inhibition of repopulation in the Fah −/− model may be due to a sensitivity to level of activation of TNF signaling, the duration of injury, or the inflammatory context in toxic liver injury. Interestingly, a recent study demonstrated that blockade of TNF signaling with etanercept promoted engraftment of transplanted hepatocytes in a rat model (Viswanathan et al 2014). Taken together, these data suggest that inhibition of TNFR1 expression or activity in hepatocytes may represent a novel strategy to promote healthy repopulation in the context of toxic liver injury.…”
Section: Resultsmentioning
confidence: 90%
“…The disparate findings with TNF signaling in promotion of regeneration after partial hepatectomy as opposed to inhibition of repopulation in the Fah −/− model may be due to a sensitivity to level of activation of TNF signaling, the duration of injury, or the inflammatory context in toxic liver injury. Interestingly, a recent study demonstrated that blockade of TNF signaling with etanercept promoted engraftment of transplanted hepatocytes in a rat model (Viswanathan et al 2014). Taken together, these data suggest that inhibition of TNFR1 expression or activity in hepatocytes may represent a novel strategy to promote healthy repopulation in the context of toxic liver injury.…”
Section: Resultsmentioning
confidence: 90%
“…Another aspect we did not consider in this study, is the use of other TNF-α-blocking agents such as adalimumab, golimumab17 or etanercept29 to determine whether one of these clinically approved monoclonal antibodies has a better efficiency and efficacy to abolish the DR and fibrosis. All these TNF-α blockers contain the IgG1 Fc portion, which on one hand improves the in vivo half-life, but on the other hand leads to unwanted effector-mediated cytotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, early clearance of transplanted cells (80–90%) from the liver is a major problem for cell engraftment. Recently, ischemia-related events involving vasoconstrictors, such as endothelin (ET)-1 (2,3), and numerous inflammatory chemokines/cytokines/receptors controlled by cell transplantation-induced expression of TNF-α were determined to play significant roles in clearance of transplanted cells (4). On the other hand, to integrate in the liver parenchyma, transplanted cells must enter the space of Disse by disruption of liver sinusoidal endothelial cells (LSEC), which requires additional interventions and further contributes in clearance of transplanted cells (5).…”
Section: Introductionmentioning
confidence: 99%
“…If such cell transplantation-related deleterious events could be controlled especially by drugs that should particularly benefit clinical applications. In preclinical animal models of cell engraftment or liver repopulation, the beneficial potential of multiple discrete drug targets was successfully demonstrated, e.g., vasodilatation of hepatic sinusoids by nitroglycerine, phentolamine, prostacyclin or ET-1 receptor blockers, bosentan (BOS) and darusentan (2,3,6), release of cytoprotective factors from hepatic stellate cells (HSC) by the cyclooxygenase inhibitors, naproxen or celecoxib (7), neutralization of TNF-α expressed by neutrophils (PMN) or Kupffer cells (KC) by etanercept (ETN) (4), and induction of injury to LSEC with cyclophosphamide or doxorubicin (8,9). Similarly, availability of safe and effective drugs with more than one desirable mechanism of action could advance cell therapy strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation